In vivo imaging rhodopsin distribution in the photoreceptors with nano-second pulsed scanning laser ophthalmoscopy - Liu, Tan; Liu, Xiaojing; Wen, Rong; Lam, Byron L.; Jiao, Shuliang (Quantitative Imaging in Medicine and Surgery, 2014)
Background: Rhodopsin is a biomarker for the function of rod photoreceptors, the dysfunction of which is related to many blinding diseases like retinitis pigmentosa and age-related macular degeneration. Imaging rhodopsin quantitatively may provide a powerful clinical tool for diagnosis of these diseases. To map rhodopsin distribution accurately in the retina, absorption by rhodopsin intermediates need to be minimized. Methods and materials: We developed nano-second pulsed scanning laser ophthalmoscopy (SLO) to image rhodopsin distribution in the retina. The system takes advantage of the light-induced shift of rhodopsin absorption spectra, which in turn affects the fundus spectral reflection before and after photobleaching. By imaging the retina twice, one in the dark-adapted state and the other one in the light-adapted state, the rhodopsin absorption change can be calculated from the differential image, which is a function of the rhodopsin concentration in the rod photoreceptors. Results: The system was successfully applied to in vivo imaging of rat retina in different bleaching conditions to verify its feasibility. Our studies showed that the differential image between the dark- and light-adapted states represents rhodopsin distribution in the retina. We also conducted a dynamic bleaching experiment to prove the importance of reducing light absorption of rhodopsin intermediates. Conclusions: The preliminary results showed that our nano-second pulsed-light SLO is promising in imaging the functional biomarker of the rod photoreceptors. By using nanosecond pulsed laser, in which one laser pulse generates one pixel of the image, the absorption of rhodopsin intermediates can be reduced.